Top-10 Tips for Getting Started with Magnetic Resonance Neurography - Chalian, Majid; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2019)
Magnetic resonance neurography (MRN), also known as MR neurography, is a dedicated imaging technique for the peripheral nerves, used both in a clinical setting and research. However, like any other new diagnostic processes, there are technical, cost, and patient selection issues to overcome as well as potential imaging pitfalls to recognize before MRN can be adopted efficiently into routine clinical practice. This review focuses on the 10 most important practical tips to get started with MRN with a view to shortening the time needed for radiologists to implement this clinically useful technique into their imaging practices.
Keywords: magnetic resonance neurography; MRN; peripheral nerve MRI; neuropathy; structured interpretation